New Gehry Technologies will enable many to boldly go where only Frank has gone before. - Snoonian, Deborah (Architectural Record)
The article reports on the establishment of Gehry Technologies (GT), a joint venture owned by Frank O. Gehry and James Glymph. Glymph has worked alongside Gehry for more than a decade. GT may also serve as a software developer, creating specialized interfaces or additional capabilities for existing design software such as CATIA, the aerospace program the firm has used on many projects.